2018
DOI: 10.1158/1940-6207.capr-18-0087
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Suppresses PGE2 and Activates AMP Kinase to Inhibit Melanoma Cell Motility, Pigmentation, and Selective Tumor Growth In Vivo

Abstract: There are conflicting epidemiologic data on whether chronic aspirin (ASA) use may reduce melanoma risk in humans. Potential anticancer effects of ASA may be mediated by its ability to suppress prostaglandin E (PGE) production and activate 5'-adenosine monophosphate-activated protein kinase (AMPK). We investigated the inhibitory effects of ASA in a panel of melanoma and transformed melanocyte cell lines, and on tumor growth in a preclinical model. ASA and the COX-2 inhibitor celecoxib did not affect melanoma ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 51 publications
2
30
1
Order By: Relevance
“…401,402 Subsequently, aspirin was demonstrated to kill melanoma, prostate, ovarian and other cancers by inhibition of PGE2 expression. [403][404][405][406] Aspirin was also reported to mediate tumor-promoting inflammation in a COX independent manner, mainly by regulating the NF-κB signaling pathway, which was initially shown as a key event relating to chronic inflammation and increased cancer risk. 407 Zhang et al showed that some aspirin-based drugs exerted anticancer activity in colon and pancreatic cancer cells by inducing ANXA1, which could prevent NF-κB binding to DNA leading to increased apoptosis and decreased proliferation.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…401,402 Subsequently, aspirin was demonstrated to kill melanoma, prostate, ovarian and other cancers by inhibition of PGE2 expression. [403][404][405][406] Aspirin was also reported to mediate tumor-promoting inflammation in a COX independent manner, mainly by regulating the NF-κB signaling pathway, which was initially shown as a key event relating to chronic inflammation and increased cancer risk. 407 Zhang et al showed that some aspirin-based drugs exerted anticancer activity in colon and pancreatic cancer cells by inducing ANXA1, which could prevent NF-κB binding to DNA leading to increased apoptosis and decreased proliferation.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Melanogenesis, a multistep and highly regulated pathway, can switch metabolism of cells from OXPHOS to anaerobic glycolysis [ 27 , 28 , 58 ] and increase mitochondrial mass [ 59 ]. For the A375 and WM3311 melanoma cell lines comparable melanin levels have been reported [ 60 , 61 ]. Thus, the melanin content of these two cell lines cannot explain differences seen in OXPHOS activity, respiration, and glycolytic activity ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, we found that NO is directly involved in the process, since inhibiting eNOS in SA/ASA-treated B16F10 cells prevented the upregulation of CHOP and ATF4, and therefore preventing apoptosis trigger. The anticancer effects of ASA on melanoma have been discussed elsewhere [63][64][65][66][67][68] , but it is the first time that involvement of UPR is presented as a mechanism for this drug anticancer property. Although most of the papers dealing with implanted tumor cells in mice use immune-compromised animals, here we opted to use wild-type immune-competent C57BL6/J mice since B16F10 cells are from the same animal origin and would not be rejected by the mice.…”
Section: Discussionmentioning
confidence: 99%